2016
DOI: 10.1177/0300060515627561
|View full text |Cite
|
Sign up to set email alerts
|

Fasting serum insulin levels and insulin resistance are associated with blood rheology in Japanese young adults without diabetes

Abstract: ObjectivesTo evaluate fasting serum insulin levels and insulin resistance, and their association with blood rheology, in Japanese young adults without diabetes.MethodsBlood samples were analysed and blood rheology was estimated using haematological parameters. Whole blood passage time was measured using a Hitachi MC-FAN© microchannel array flow analyser.ResultsOut of 151 subjects (mean age, 24.1 ± 1.5 years), fasting serum insulin levels and insulin resistance (using homeostasis model assessment-estimated insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
(115 reference statements)
2
10
1
Order By: Relevance
“…Studies using MC-FAN indicated that mean WBPT values in patients without diabetes mellitus or healthy controls are approximately 40 s degree [ 23 , 24 ], whereas mean WBPT values in this study were 62.5 s. Thus, these results indicated that the impairment of hemorheology in patients with type 2 diabetes mellitus was progressive compared with that in nondiabetic or healthy controls. Furthermore, independent associations between WBPT and hs-cTnT levels suggest that the impairment of hemorheology is an important factor for the progression of subclinical myocardial injury or primary cardiovascular incidence in patients with type 2 diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 55%
“…Studies using MC-FAN indicated that mean WBPT values in patients without diabetes mellitus or healthy controls are approximately 40 s degree [ 23 , 24 ], whereas mean WBPT values in this study were 62.5 s. Thus, these results indicated that the impairment of hemorheology in patients with type 2 diabetes mellitus was progressive compared with that in nondiabetic or healthy controls. Furthermore, independent associations between WBPT and hs-cTnT levels suggest that the impairment of hemorheology is an important factor for the progression of subclinical myocardial injury or primary cardiovascular incidence in patients with type 2 diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 55%
“…A recent Japanese clinical study using MC-FAN indicated that the mean WBPT values in patients without diabetes mellitus and in healthy control subjects were 39.9 and 37.1 s, respectively [19,20]. The mean WBPT of the patients in the present study was 61.3 s, indicating that blood rheology was impaired in patients with type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 48%
“…Several cross-sectional studies have assessed WBPT in healthy populations or in patients with cardiovascular risk factors, with the results suggesting that the cut-off value for cardiovascular risk is 50 - 70 s [ 10 , 16 - 18 ]. Based on these previous results, the present study prospectively divided the participants into three groups according to two simple cut-off levels of 50 s and 70 s. The results showed that participants with WBPT > 70 s were a population at high risk of primary cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…MC-FAN can be used to measure the whole blood passage time (WBPT). Cross-sectional studies have reported significant relationships between an increase in WBPT and cardiovascular risk factors or cardiovascular disease [ 7 - 10 ]. However, there have been no prospective studies of the clinical usefulness of WBPT as a predictor of cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%